PWE-034 Should we be diagnosing coeliac disease in the elderly?. (June 2019) - Marks, Lauren; Rej, Anupam; Kurien, Matthew; Rees, Michael; Cross, Simon; Hadjivassiliou, Marios; Sanders, David
Abstract : Introduction: Coeliac disease (CD) is common, but is underdiagnosed in the elderly due to lack of physician awareness and heterogeneity of presentation. We aimed to establish whether there has been a change in the diagnosis of CD in the elderly (over 65 years old) from 1990 until present day, as well as the clinical and histopathological features of CD in old vs. young adults. Methods: Newly diagnosed CD patients were prospectively recruited from the Coeliac Specialist Clinic at the Royal Hallamshire Hospital, Sheffield, between 2008 and 2017. All patients had villous atrophy (VA) on biopsy, positive coeliac serology (IgA-tissue transglutaminase and IgA-endomysial antibodies) and compatible Human Leukocyte Antigen (HLA) typing. Additionally, patients were retrospectively identified from 1990 to 2008 to determine the trend in elderly CD diagnostic frequency over time. Results: 1605 patients with CD were recruited (n=644 prospectively, n=961 retrospectively). Of these, 208 patients (13.0%) were diagnosed over the age of 65 years between 1990 and 2017. The proportion of elderly CD diagnoses increased from 0% (n=0/11) in 1990–1991 to 18.7% (n=41/232) in 2016–2017 (p<0.001). The male to female ratio decreased with increasing diagnostic age from 1.71:1 in the 18–34 age group to 1.02:1 in the over 65 age group (p<0.001). Younger patients more commonly presented with fatigue (p<0.001) and gastrointestinal symptoms including diarrhoea (p=0.005), abdominal pain (p=0.019), and IBS-type symptoms (p=0.008), as seen in table 1 . Older people more frequently presented with B12 deficiency (p=0.037) and had milder degrees of VA than younger patients (p=0.005). Conclusions: Coeliac disease is common in elderly patients but gastrointestinal symptoms occur less frequently than in younger individuals. Elderly patients tend to present with a milder degree of VA. This questions the utility of active case finding in this age group, as a gluten free diet may not be the most appropriate management in this cohort.